2022
DOI: 10.3390/ijms23158619
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Dicyanomethylene-Based Fluorescent Probes for the Detection of β-Amyloid in Alzheimer’s Disease: A Theoretical Perspective

Abstract: Motivated by the growing demand for target chemosensors designed with diagnostic or therapeutic capability for fibrils related to amyloidosis diseases, we investigated in the present work the response mechanism of dicyanomethylene-based fluorescent probes for amyloid fibril using a combined approach, including molecular docking, quantum mechanics/molecular mechanics (QM/MM), and the quantum chemical method. Various binding modes for the probes in β-amyloid (Aβ) are discussed, and the fibril environment-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Dicyanomethylene derivatives [ 30 , 141 , 142 ]. A well-known representative is the PET probe FDDNP ( Figure 23 a) [ 143 ], used for research purposes.…”
Section: Molecular Design Of Mri Fibril-binding Probesmentioning
confidence: 99%
“…Dicyanomethylene derivatives [ 30 , 141 , 142 ]. A well-known representative is the PET probe FDDNP ( Figure 23 a) [ 143 ], used for research purposes.…”
Section: Molecular Design Of Mri Fibril-binding Probesmentioning
confidence: 99%
“…Experimentally, dicyanomethylene has shown potential for selective binding affinity to Aβ aggregates, along with excellent fluorescence enhancement. 30 Cui et al reported different NIRF probes containing the dicyanomethylene group for targeting Aβ deposits. In the initial series, N,N′-dimethylamino group attached to the benzene ring was chosen as the electron donor and the dicyanomethylene group as the electron acceptor, interconnected by conjugated double bonds (DNIRs).…”
Section: ■ Dicyanomethylene Derivativesmentioning
confidence: 99%
“…The report proposed a comprehensive consideration of binding affinity, where the efficiency of the dicyanomethylene-based fluorescent probe for Aβ species could be improved through the combined πconjugate extension and adjusting the ability of electron donating/accepting groups of the fluorophore. 30 The NIRF probe was also reported with a selective turn-on fluorescence effect when it bound to the target, which may improve the detection of Aβ species and enable in vivo molecular imaging quantitatively. The fluorescence tends to emit, selectively turned on, by the rotatable donor−acceptor bond when the intramolecular rotational relaxation about the donor−acceptor bond is constrained.…”
Section: ■ Dicyanomethylene Derivativesmentioning
confidence: 99%
See 2 more Smart Citations